THE TRANSLATION OF STATE VERBS IN GONE WITH THE WIND INTO LALU BERSAMA ANGIN : NATURAL SEMANTIC METALANGUAGE APPROACH - Desak Ayu Krisna Dewi; I Nengah Sudipa; Ni Wayan Sukarini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
This writing aims to reveal what translation techniques are applied in translating state verbs and. to analyze how meanings are retained from source language text to target language text in the novel. It is also highlights the correlation between translation and semantic primes studies. The data focuses on the translation of state verbs taken from the novel Gone with the Wind into Lalu Bersama Angin written by Margareth Mitchell by applying the Natural Semantic Metalanguage approach. This study used a qualitative method means the data are collected by observation and note taking process. There are two main theories applied in this study they are the theory of the Natural Semantic Metalanguage (NSM) and the theory of translation techniques. NSM is used for a term of reference to break the concept or word down by using a small collection of semantic primes in order to make the differences clear among the meanings of state verbs in the form of paraphrases. The theory of translation techniques by Molina and Albir (2002) is applied in order to discuss the techniques of translation used in state verb lexicon. The result found literal translation is dominating the translation technique that indicates the direct transfer SL text word per word. There is also found translation by applying transposition involved the changes in word class. Another techniques found are modulation technique which change the point of view and discursive creation which deal with establishing a temporary equivalence that is totally unpredictable out of context and the last translation technique found: particularization technique. The findings of the meaning retained from SL text into TL text are based on the subtype of state verb and explicated comprehensively using NSM approach. The categorization of state verb including type of cognition (e.g believing), type of know (e.g remember), type of feel (e.g loved), type of see (e.g stared), type of want (e.g anxious to get). There is also found several phenomena caused by the translation process. The change of intensity of state verb is the one from a higher intensity of meaning to a lower in accordance with the context such as from SL text stared into TL text menatap. The change of type of state verb also found; from type of feel into the type of want such as anxious into menginginkan.